2018
DOI: 10.1182/blood-2017-11-814681
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies induce thrombosis by PP2A activation via apoER2-Dab2-SHC1 complex formation in endothelium

Abstract: In the antiphospholipid syndrome (APS), antiphospholipid antibody (aPL) recognition of β2 glycoprotein I promotes thrombosis, and preclinical studies indicate that this is due to endothelial nitric oxide synthase (eNOS) antagonism via apolipoprotein E receptor 2 (apoER2)-dependent processes. How apoER2 molecularly links these events is unknown. Here, we show that, in endothelial cells, the apoER2 cytoplasmic tail serves as a scaffold for aPL-induced assembly and activation of the heterotrimeric protein phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 89 publications
0
55
0
2
Order By: Relevance
“…Lo anterior sugiere que el incremento del estrés oxidativo inducido por los anticuerpos antifosfolípidos de los pacientes con síndrome antifosfolípido, altera la funcionalidad de la sintasa endotelial de óxido nítrico; sin embargo, no es claro si estos eventos se asocian con trombosis 36 . No obstante, se sabe que, en el endotelio tratado con anticuerpos antifosfolípidos de pacientes con trombosis, se reduce la fosforilación de dicha sintasa endotelial, dependiendo del receptor 2 de la apopolipoproteína E 37 . En estudios posteriores, podría considerarse la evaluación de una posible relación del estrés oxidativo y la disminución de la activación de la sintasa endotelial de óxido nítrico, ya que ambos eventos son inducidos por anticuerpos antifosfolípidos de pacientes con síndrome antifosfolípido que tienen trombosis, como se encontró en este trabajo y en otros reportes 37 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Lo anterior sugiere que el incremento del estrés oxidativo inducido por los anticuerpos antifosfolípidos de los pacientes con síndrome antifosfolípido, altera la funcionalidad de la sintasa endotelial de óxido nítrico; sin embargo, no es claro si estos eventos se asocian con trombosis 36 . No obstante, se sabe que, en el endotelio tratado con anticuerpos antifosfolípidos de pacientes con trombosis, se reduce la fosforilación de dicha sintasa endotelial, dependiendo del receptor 2 de la apopolipoproteína E 37 . En estudios posteriores, podría considerarse la evaluación de una posible relación del estrés oxidativo y la disminución de la activación de la sintasa endotelial de óxido nítrico, ya que ambos eventos son inducidos por anticuerpos antifosfolípidos de pacientes con síndrome antifosfolípido que tienen trombosis, como se encontró en este trabajo y en otros reportes 37 .…”
Section: Discussionunclassified
“…No obstante, se sabe que, en el endotelio tratado con anticuerpos antifosfolípidos de pacientes con trombosis, se reduce la fosforilación de dicha sintasa endotelial, dependiendo del receptor 2 de la apopolipoproteína E 37 . En estudios posteriores, podría considerarse la evaluación de una posible relación del estrés oxidativo y la disminución de la activación de la sintasa endotelial de óxido nítrico, ya que ambos eventos son inducidos por anticuerpos antifosfolípidos de pacientes con síndrome antifosfolípido que tienen trombosis, como se encontró en este trabajo y en otros reportes 37 .…”
Section: Discussionunclassified
“…At both time points, these cells showed activation of Akt (measured by the p-Ser 473 Akt/total Akt ratio) with an attenuation at 120 min ( Figure 2L), and displayed a ~30% increase in levels of ApoER2 ( Figure 2L). In contrast, CD2AP-depleted cells treated with Reelin displayed at both time points an hyperactivation of the kinase, known to interfere with ApoER2 recycling 69,70 , and consistently, lower levels of the receptor ( Figure 2L). Taken together, our data revealed that CD2AP is in complex with ApoER2, and regulates both the levels and Reelin-dependent signaling of the receptor in BECs.…”
Section: No Interaction Was Found Between Cd2ap and Picalm (Phosphatimentioning
confidence: 98%
“…The canonical Reelin signaling pathway involves the binding of Reelin to ApoER2 and this leads to the phosphorylation of the adaptor protein disabled-1 (Dab1), and subsequently to the phosphorylation/activation of protein kinase B (Akt) at Ser473 65 . This signaling is dampened by Dab2, an adaptor protein that strongly associates with CD2AP 66 and ApoER2 67,68 , and is involved in the recycling of the receptor through inactivation of Akt 69 . BECs transfected with control siRNA and treated with Reelin for 30 and 120 min undergo signaling via the canonical pathway.…”
Section: No Interaction Was Found Between Cd2ap and Picalm (Phosphatimentioning
confidence: 99%
“…In particular, attenuation of eNOS activation by aPL was mediated by reduced phosphorylation of eNOS serine 1179. This inhibition of eNOS phosphorylation was shown to be dependent upon protein phosphatase 2A (PP2A), β2GPI, and apolipoprotein E receptor 2 (ApoER2) (Figure 1A) (Ramesh et al, 2011; Sacharidou et al, 2018a). Furthermore, aPL inhibition of eNOS activity contributes to thrombus formation, increased leukocyte adhesion, and alterations in vascular tone.…”
Section: Impaired Synthesis Of Antithrombotic Factors In Apsmentioning
confidence: 99%